La Definición de Cuidados Paliativos y sus alcances en el derecho argentino (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
In this paper I investigate what is understood by palliative care in the laws and legal norms that regulate and guarantee access to these services in Argentina to evaluate whether they meet the definition of PC developed by the WHO and the International Association of Hospice and Palliative Care. This research will help us verify whether the regulations contribute or hinder access to PC for people in vulnerable situations due to suffering associated with a serious illness. The analysis focuses on four criteria: the subjective scope of the CP, the characterization of the diseases covered, the type of approach and the spectrum of problems protected. The conclusión is that the norms in Argentina on PC reflect the new conception of PC, although challenges remain linked to the scope of the Mandatory Medical Program and the articulation of PC programs so that they reach both oncological and non-oncological patients.
Keywords: Palliative care; Right to health; Federal regulations.